Feeling of fever is a feature of psychiatric illness in our patients (TAJ: Journal of Teachers Association, 2018)
The patients present to their physician with their somatic symptoms which are attributable to some medical illness. This is not always true. Sometimes a few patients present with the complaints of prolonged fever for months to year duration. As fever is an important vital sign it gains attention of the physician to work up and reveal the cause. In this study apparently healthy patients who complained of prolonged fever were clinically assessed, routine investigations were done and found normal. Then they were provided with a temperature chart to note down body temperature with a thermometer for one week from first visit. Afebrile such fifty patients complaining of fever were referred to psychiatrist for evaluation. All patients showed some sort of psychiatric illness. 20 (40%) were of generalized anxiety disorder, 10 (20%) depression, 5 (10%) mixed anxiety and depression, 5 (10%) obsessive compulsive disorder, 10 (20%) somatoform disorder. The practicing physician may encounter many patients of prolonged fever which are not febrile at all so they need psychiatric assessment and treatment to relieve their distress.TAJ 2014; 27(1): 1-3